2014
DOI: 10.12693/aphyspola.125.526
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Polymer Based Syntactic Foam for High Temperature Applications

Abstract: Syntactic foams are one of the most widely used close cell structured foams. They are used in applications for naval, aeronautical, aerospace, civil, industrial, and automotive engineering due to good acoustical attenuation, excellent strength to weight ratio, vibration isolation, and dielectric properties. These foams are fabricated by incorporation of hollow particles in a matrix material. The most preferred matrix materials are polymers. In this study silicone resin (useful temperature range −53• C to 232• … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The filler material selected follows the methods and findings of Yazici et al. for its effectiveness in high temperature applications [21]. High temperature-resistant closed cell syntactic foam was produced in house using platinum cured silicone resin and A20/1000 Glass Bubbles supplied by 3M Company following the methods and findings by.…”
Section: Materials and Specimenmentioning
confidence: 99%
See 1 more Smart Citation
“…The filler material selected follows the methods and findings of Yazici et al. for its effectiveness in high temperature applications [21]. High temperature-resistant closed cell syntactic foam was produced in house using platinum cured silicone resin and A20/1000 Glass Bubbles supplied by 3M Company following the methods and findings by.…”
Section: Materials and Specimenmentioning
confidence: 99%
“…It was observed that in the cellular core, back face side foam filling improved the air shock pressure mitigation without increasing the weight. Novel materials, such as syntactic foams, show improved energy absorption and may even be used in some high-temperature applications [20][21][22][23]. Syntactic foams are comprised of particles used to enhance or modify material properties, and the particles are suspended in a matrix material ranging from rubber or elastomer, ceramics, and even metal.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al added hollow polymer and carbon microspheres prepared by spray drying into phenolic to fabricate low‐density syntactic foams and investigated the compressive strength. Yazici et al developed glass bubble/silicon rubber composites and detected compressive properties with respect to particle percentage variation under high and room temperatures. Tagliavia et al studied the effect of wall thickness and volume fraction of hollow inclusions on flexural strength of vinyl ester syntactic foams.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone rubber foam is an elastomer combining the advantages of silicone rubber and foam, which exhibits a variety of excellent properties, such as low density, heat and cold resistance, good electrical insulation, and biocompatibility, and has wide application in the areas of aerospace, transportation, and medical treatment, etc. [1][2][3][4] The properties of silicone rubber foam are highly dependent on the cell size and cell density, which are relevant to the use of foaming agents that can be either chemical or physical in the preparation of silicone rubber foam, which are crucial and necessary. For well dispersion, easy controlled decomposition temperature, and producing foam with uniform cell structure, chemical foaming is widely used in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone rubber foam is an elastomer combining the advantages of silicone rubber and foam, which exhibits a variety of excellent properties, such as low density, heat and cold resistance, good electrical insulation, and biocompatibility, and has wide application in the areas of aerospace, transportation, and medical treatment, etc …”
Section: Introductionmentioning
confidence: 99%